HYMN O SŁOWIE ROMANA BRANDSTAETTERA, CZYLI CO JEST PRZED WSZYSTKIM? - Ojcewicz, Grzegorz (Acta Neophilologica, 2012)
The article presents a translation experiment done by Roman Brandstaetter while translating the prologue initiating the Gospel of John. Not only did the translator change the traditional form of naming the prologue About the Word or The Eternal Word and propose a lofty genre one – Hymn to the Word – but also altered past tense form “was” for present “is” which constituted the core of his experiment. That alteration revealed and established the understanding of eternal time by the Israelis in the times of John the Evangelist. Following the innovative path of Brandstaetter the author of the article suggested another transformation – exchange of “Word” for “Ghost” – in order to create a new experimental adaptation of that work as well as to emphasize the timelessness of Hymn to the Word.